Energy efficiency of blower heater non-purge compressed air dryers. (9th July 2021) - Botts, Alexandra; Gopalakrishnan, Bhaskaran; Nimbarte, Ashish; Currie, Kenneth R.; Karki, Vivash
This research focuses on twin tower regenerative closed loop desiccant dryers, specifically: blower heater non-purge (BHNP) with and without cooling water pumps, compressed-air heater purge (CHP), blower heater purge (BHP) and pressure swing heaterless (PSH). The research was conducted by collecting and analysing real time current draw data on air compressors and associated dryers at eight different facilities (13 air compressors) in terms of energy, power and cost. A decision tool was developed to depict the operational characteristics (power, energy and cost) of each type of dryer if used in conjunction with the selected compressor system. Finally, this research, on an equivalent normalised basis, compared and contrasted the different types of dryers in terms of performance and cost. The research concluded that of the five types of desiccant dryer types observed the most energy efficient was the BHNP (with cooling water pump), subject to the operational conditions.